Social sciences and the study of the migratory phenomenon - Valencia León, Ivonne Teresa (2018)
The migratory phenomenon is one of the social problems with the most impact in the world today, as it alters the dynamics of societies of origin of immigrants but also those of arrival. Our analysis springs from the idea that migration must be studies from an ample perspective and not necessarily from a single discipline. In that sense, the present article aims to examine the theoretical perspective that social sciences have of the migratory phenomenon. This analysis helps to understand the characteristics of migration, as well as its effects. This work is composed of four parts. In the first one, we approach the study of migration from the disciplines within the social sciences; in the second, we analyze the integrated perspective for the study of migrations; in the third, we analyze the dimensions and repercussions of migration in social life; and finally, in the las part, we provide some reflections on the implications of the theory of complexity in the multidisciplinary study of migration to arrive at the necessity for a perspective that can develop a social science of migrations